Crystal structure of 4-chloro-N′-[(1E)-(2-nitrophenyl)methylidene]benzohydrazide, C14H10ClN3O3 - Al-Wahaibi Lamya H.; Blacque Olivier; Tiekink Edward R. T.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures)
C14H10ClN3O3, triclinic, P1 (no. 1), a = 4.8813(2) Å, b = 6.7806(2) Å, c = 10.3135(2) Å, α = 98.101(2)∘ $98.101{\left(2\right)}^{° }$ , β = 94.174(2)∘ $94.174{\left(2\right)}^{° }$ , γ = 97.612(3)∘ $97.612{\left(3\right)}^{° }$ , V = 333.515(18) Å3, Z = 1, Rgt ${R}_{gt}$ (F) = 0.0270, wRref $wR_{ref}$ (F2) = 0.0743, T = 160 K.